2018
DOI: 10.1186/s40854-018-0094-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and financing adaptation by farmers in northern Nigeria

Abstract: This paper examines farmers' perceptions of their exposure to climate change in rural northern Nigeria. It also examines whether there is a significant relationship between the exposure of farmers to climate change and their need for financial access as an adaptation strategy. Questionnaires were administered to 320 respondents in rural communities in northern Nigeria. Descriptive analysis shows that rural farmers are affected by climate change through increased temperature, prolonged dry seasons, floods, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Another reason informing the focus of this paper is due to recent evidence on how drought and desertification have contributed to flaming the conflict between farmers and herders in rural northern communities in northern Nigeria. Many farming communities have been affected by climate change in rural northern Nigeria (see Abraham and Fonta 2018), hence, has made many of the youths, women and children so displaced to be available as recruits for the radical sects such as the Boko Haram and other armed group in the sub region (see Avery 2018). By examining whether the poorest income quintile benefit from programs aimed at increasing their access to financial services in rural northern Nigeria therefore, this paper contributed towards providing field facts that would help redirect the focus of government policy in order to achieve inclusive growth and development.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Another reason informing the focus of this paper is due to recent evidence on how drought and desertification have contributed to flaming the conflict between farmers and herders in rural northern communities in northern Nigeria. Many farming communities have been affected by climate change in rural northern Nigeria (see Abraham and Fonta 2018), hence, has made many of the youths, women and children so displaced to be available as recruits for the radical sects such as the Boko Haram and other armed group in the sub region (see Avery 2018). By examining whether the poorest income quintile benefit from programs aimed at increasing their access to financial services in rural northern Nigeria therefore, this paper contributed towards providing field facts that would help redirect the focus of government policy in order to achieve inclusive growth and development.…”
Section: Empirical Literaturementioning
confidence: 99%
“…6 Purpose for which Credit was sought by Household by Proportion (%). Source: Abraham and Fonta (2018)…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…We recommend more rigorous efforts of promoting awareness in synergy with climate-smart adaptation strategies. This is important because farmers' perceptions and/or awareness of climate change guide their adaptation strategies [47,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we assume increasing and convex iso-elastic inverse supply functions: in equilibrium, wages and the cost of capital increase with the amount of capital and labor used by the fishery. In previous climate change adaptation studies on agriculture, access to financing has been found to be a major determinant [79]. Fuel supply is perfectly elastic, and prices are determined on the world market.…”
Section: Methodsmentioning
confidence: 99%